The THE EFFECT OF INTEGRATED VALUE ON STUDENT PURCHASE INTENTION ITEMS IN THE PUBGM GAME IN BONTANG - Shania Pandean; David Paul Elia Saerang; Regina Trifena Saerang (Universitas Sam Ratulangi, 2023)
This research aims to analyze the effect of integrated value on student purchse intention in the pubgm game at Bontang. The independent variables used in this research are enjoyment value, visual authority value, and monetary value, while the dependent variable is purchase intention. This research uses primary data obtained from questionnaires measured with the Likert scale. The sample is the esport game player in Bontang. Test instruments are performed using Validity and Reliability Tests. The regression results show that monetary value a positive and significant effect on student purchase intention in the pubgm game, whileenjoyment value and visual authority value exerts no influence on purchase intention. Keywords: enjoyment value, visual authority value, monetary value and purchase intention